2009
DOI: 10.5194/angeo-27-4125-2009
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities of mesospheric tides and equatorial electrojet strength during major stratospheric warming events

Abstract: Abstract. The present study demonstrates the relationship between the high latitude northern hemispheric major sudden stratospheric warming (SSW) events and the reversal in the afternoon equatorial electrojet (EEJ), often called the counter-electrojet (CEJ), during the winter months of 1998-1999, 2001-2002, 2003-2004 and 2005-2006. As the EEJ current system is driven by tidal winds, an investigation of tidal variabilities in the MF radar observed zonal winds during the winters of 1998-1999 and 2005-2006 at 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 26 publications
4
105
0
1
Order By: Relevance
“…The low-latitude ionospheric response to sudden stratospheric warmings (SSWs) has been an area of extreme interest in recent years [e.g., Vineeth et al, 2009;Chau et al, 2009Chau et al, , 2010Sridharan et al, 2009;Goncharenko et al, 2010a, b;Fejer et al, 2010Fejer et al, , 2011Yue et al, 2010;Rodrigues et al, 2011;Liu et al, 2011;Park et al, 2012;Yamazaki et al, 2012a, b]. These events are characterized by large-scale metereological changes in the winter polar atmosphere, driven by the rapid growth of upward propagating quasi-stationary planetary (Rossby) waves, rapid growth of waves from the polar troposphere, and their interaction with the mean circulation, that last for several days or even a few weeks [e.g., Matsuno, 1971;Andrews et al, 1987;Liu and Roble, 2002;Holton, 2004].…”
Section: Lunar Tidal Effects During Sudden Stratospheric Warmingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-latitude ionospheric response to sudden stratospheric warmings (SSWs) has been an area of extreme interest in recent years [e.g., Vineeth et al, 2009;Chau et al, 2009Chau et al, , 2010Sridharan et al, 2009;Goncharenko et al, 2010a, b;Fejer et al, 2010Fejer et al, , 2011Yue et al, 2010;Rodrigues et al, 2011;Liu et al, 2011;Park et al, 2012;Yamazaki et al, 2012a, b]. These events are characterized by large-scale metereological changes in the winter polar atmosphere, driven by the rapid growth of upward propagating quasi-stationary planetary (Rossby) waves, rapid growth of waves from the polar troposphere, and their interaction with the mean circulation, that last for several days or even a few weeks [e.g., Matsuno, 1971;Andrews et al, 1987;Liu and Roble, 2002;Holton, 2004].…”
Section: Lunar Tidal Effects During Sudden Stratospheric Warmingsmentioning
confidence: 99%
“…The initial studies on arctic SSW effects on the equatorial upper atmosphere found large, multiday mesospheric wind changes and afternoon reversals of the equatorial electrojet [e.g., Stening et al, 1996;Vineeth et al, 2009;Sridharan et al, 2009]. Chau et al [2009] showed large daytime semidiurnal perturbations lasting for several days in the F-region vertical drift velocities over Jicamarca during the 2008 minor warming event.…”
Section: Lunar Tidal Effects During Sudden Stratospheric Warmingsmentioning
confidence: 99%
“…Vineeth et al [2009] suggested that SSWs lead to higher occurrence of quasi 16 day periodicity of equatorial counterelectrojets and that stronger counterelectrojets are associated with more intense warmings. Sridharan et al [2009] used magnetic field and mesospheric wind measurements in the Indian region to show that major arctic SSW events affect the day-to-day variability of equatorial counterelectrojets through the enhancement of semidiurnal tides.…”
Section: Introductionmentioning
confidence: 99%
“…The westward currents manifested during some instances of CEJs may be caused by reversal of the interplanetary magnetic field (IMF-Bz) component from south to north (Rastogi 1974;Sizova 2002;Francisca et al 2013) and or atmospheric tidal effects (Bhargava et al 1980;Somayajulu et al 1993;Sridharan et al 2002). Recent studies show that rise in atmospheric temperature connected with the phenomena of sudden stratospheric warming (SSW) exhibits positive correlation with occurrences of CEJs (Matsuno 1971;Liu and Roble 2002;Sridharan et al 2009). …”
Section: The Counter Electrojetmentioning
confidence: 99%